A lithium iron phosphate positive electrode material and its preparation method and application
By using secondary particle size differences in the preparation of lithium iron phosphate positive electrode material for particle grading, the problem of inconsistent performance of the material after mixing and blending of different primary particles is solved, high compaction density and uniform carbon coating are achieved, and the electrochemical performance of the material is improved.
Patent Information
- Application Number
- CN202411936191.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-01
AI Technical Summary
After the existing lithium iron phosphate positive electrode materials are mixed with different primary particles, the carbon coating is uneven and the particle size is large, resulting in inconsistent material performance.
Particle grading is performed using secondary particle size differences. By dividing the mixed slurry into the first slurry and the second slurry, and undergoing differentiated spraying treatment and sintering, a lithium iron phosphate material with clear particle grading is prepared.
It realizes high compaction density and uniform carbon coating of lithium iron phosphate materials, improves the consistency and electrochemical performance of the material, and is suitable for lithium-ion batteries.
Smart Images

Figure CN119742345A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium iron phosphate positive electrode material and a preparation method and application thereof. Background Art
[0002] Secondary batteries have the advantages of sustainable use and price advantages, and are widely used in power batteries, energy storage and other fields. Among them, lithium iron phosphate, the positive electrode material of lithium-ion batteries, has become the most promising positive electrode material due to its low cost, environmental friendliness, and excellent safety performance. The energy density of the battery is closely related to the compaction density of the electrode material. Under the conditions of fixed battery specifications and process conditions, the greater the compaction density, the higher the capacity of the single cell and the lower the cost of the single cell. Specifically, a higher material density means that the electrode can store more charge per unit volume, thereby increasing the energy density of the battery; at the same time, the increase in compaction density can increase the mass of active materials per unit volume, thereby increasing the capacity of the battery.
[0003] The compaction density of lithium iron phosphate materials is closely related to the particle size distribution. When the sintering temperature is high, the material is severely overburned as a whole, and large-size particles are distributed more. The compaction density of the material increases, and the electrical performance is limited. When the sintering temperature is low, the overall particles of the material are small, and the compaction density of the material is low. Therefore, appropriate size particle grading is one of the methods to achieve lithium iron phosphate materials to maintain excellent electrical performance at high compaction density. Most existing technologies achieve lithium iron phosphate grading based on primary particle size differences, such as mixing different sand-milled particle sizes and blending lithium iron phosphate with different particle sizes. However, there are problems such as uneven carbon coating effect leading to poor consistency, which affects the performance of the material.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The first purpose of the present invention is to provide a method for preparing a lithium iron phosphate positive electrode material, which can effectively solve the defects of uneven carbon coating and large particle size differences in the lithium iron phosphate material after different primary particles are mixed; the present invention performs particle grading based on the difference in secondary particle size, and further based on the difference in particle growth rate of powders with different secondary particle sizes during sintering, thereby preparing a lithium iron phosphate material with clear particle grading.
[0006] The second object of the present invention is to provide a lithium iron phosphate material prepared by the method for preparing the lithium iron phosphate positive electrode material.
[0007] A third object of the present invention is to provide a lithium ion battery.
[0008] A fourth object of the present invention is to provide an electrical device.
[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0010] A method for preparing a lithium iron phosphate positive electrode material comprises the following steps:
[0011] (1) preparing a solution containing a phosphorus source, an iron source, a lithium source, a carbon source and an additive, and grinding the solution to obtain a mixed slurry; dividing the mixed slurry into a first slurry and a second slurry;
[0012] (2) subjecting the first slurry to a first spray treatment to obtain a first spray material;
[0013] (3) after the second slurry is fully mixed with a surfactant, a second spraying treatment is performed to obtain a second spray material;
[0014] (4) The first spray material and the second spray material are mixed, sintered, and crushed to obtain lithium iron phosphate.
[0015] A lithium iron phosphate is prepared according to the preparation method of the lithium iron phosphate positive electrode material.
[0016] A lithium ion battery comprises the lithium iron phosphate.
[0017] An electrical device comprises the lithium-ion battery.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] (1) The present invention achieves the lithium iron phosphate particle grading effect based on the difference in secondary particle size by distributing the slurry containing the raw materials, performing differentiated spray treatment and then calcining. Compared with the process of mixing primary particles with differences, the preparation method of the present invention can obtain lithium iron phosphate positive electrode materials with good consistency, high compaction density and uniform carbon coating effect, and has the advantages of simple method and easy promotion. At the same time, the lithium iron phosphate prepared based on the present invention has good electrochemical performance in the field of lithium ion batteries.
[0020] (2) The present invention introduces a surfactant component before spraying a portion of the slurry. On the one hand, it is beneficial to reduce the slurry viscosity and the secondary particle size. On the other hand, it decomposes at high temperature to generate organic small molecules, which have a certain synergistic effect with the carbon source, which is beneficial to the pore formation of the positive electrode material, controls the grain morphology, inhibits the growth of grains, and makes the small particle size more uniform, thereby achieving the excellent electrical performance of the lithium iron phosphate material under high compaction density. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 Provides a particle size distribution diagram of the lithium iron phosphate material of Example 1 of the present invention;
[0023] Figure 2 A scanning electron microscope image of the lithium iron phosphate material of Example 1 of the present invention is provided. DETAILED DESCRIPTION
[0024] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but those skilled in the art will appreciate that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially. In addition, the terms "first", "second" and "third" are only used for descriptive purposes and cannot be interpreted as indicating or implying relative importance.
[0025] A first aspect of the present invention is to provide a method for preparing a lithium iron phosphate positive electrode material.
[0026] (1) preparing a solution containing a phosphorus source, an iron source, a lithium source, a carbon source and an additive, and grinding the solution to obtain a mixed slurry; dividing the mixed slurry into a first slurry and a second slurry;
[0027] (2) subjecting the first slurry to a first spraying treatment to obtain a first spray material;
[0028] (3) after the second slurry is fully mixed with a surfactant, a second spraying treatment is performed to obtain a second spray material;
[0029] (4) The first spray material and the second spray material are mixed, sintered, and crushed to obtain lithium iron phosphate.
[0030] Based on the above main method steps, it can be known that the present invention provides a method for preparing lithium iron phosphate based on the difference in secondary particle size to achieve particle grading. In this field, primary particles generally refer to the particle size of a single fine grain, also known as the original particle size or initial particle size; secondary particles refer to the particle size of particles after particle agglomeration; in the present invention, two spray materials with different secondary particles are obtained through two spray treatment routes, and a synergistic grading is formed based on the huge differences in particle size, porosity and specific surface area between the two, thereby preparing a lithium iron phosphate positive electrode material with a high compaction density.
[0031] As a preferred embodiment, the phosphorus source includes at least one of iron phosphate, lithium monohydrogen phosphate, lithium dihydrogen phosphate, ammonium phosphate or ammonium dihydrogen phosphate.
[0032] As a preferred embodiment, the iron source includes at least one of ferric phosphate, ferric oxide, ferroferric oxide, ferric citrate or ferrous oxalate. It is worth noting that the ferric phosphate can be used as the phosphorus source and the iron source at the same time.
[0033] As a preferred embodiment, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium citrate or lithium dihydrogen phosphate.
[0034] As a preferred embodiment, the carbon source includes at least one of glucose, sucrose, citric acid, polyethylene glycol, starch or cellulose.
[0035] As a preferred embodiment, the additive includes a compound containing one or more of titanium, niobium, magnesium or zirconium; it is understandable that the present invention can use one or more of the above four elements to dope and modify the lithium iron phosphate.
[0036] As a more preferred embodiment, when the doped modified element is titanium (Ti), the additive includes titanate, titanium dioxide or titanium tetrachloride, and titanium dioxide is further preferred. The titanium element can reduce the crystal size of lithium iron phosphate, improve the material conductivity and ion diffusion rate, thereby improving the charge and discharge rate and anti-polarization ability. At the same time, the titanium element can also improve the stability of the oxide film on the surface of lithium iron phosphate and enhance battery safety.
[0037] As a more preferred embodiment, when the doped modified element is niobium (Nb), the additive includes niobium oxide, niobium chloride or niobium acetate, and niobium pentoxide is further preferred; the crystal structure of the niobium element is used to increase the embedding and extraction efficiency of lithium ions in the lithium iron phosphate material, thereby improving the energy density of the lithium iron phosphate and extending the service life of the battery.
[0038] As a more preferred embodiment, when the element contained in the dopant is magnesium (Mg), the dopant includes magnesium oxide, magnesium hydroxide, magnesium chloride, magnesium carbonate or magnesium nitrate, and magnesium oxide is further preferred; the magnesium element increases the coexistence concentration of iron in different valence states, thereby improving the conductivity, specific capacity and cycle performance.
[0039] As a more preferred embodiment, when the element contained in the dopant is zirconium (Zr), the additive includes zirconium oxide, zirconium carbonate or zirconium acetate, and zirconium oxide is further preferred; the zirconium element can effectively inhibit the polarization phenomenon of the lithium iron phosphate electrode, increase the electrode surface area, promote the transport of the electrolyte, and thus effectively increase the capacity of the battery, and improve the long-term stability and service life of the battery.
[0040] As a preferred embodiment, in the solution of step (1), the solvent is water, preferably deionized water; the solid content of the solution is 20% to 50%, including but not limited to any one of 20%, 25%, 30%, 35%, 40%, 45%, 50% or a numerical range consisting of any two of them; it is understandable that those skilled in the art can adaptively adjust the solid content of the solution within the above range based on the dispersibility and particle size of the selected raw materials; in some optional cases, before grinding, methods such as oscillation, stirring, centrifugation, ultrasound, etc. can be used to assist in obtaining a uniformly dispersed solution system.
[0041] As a preferred embodiment, in the solution of step (1), the molar ratio of lithium atoms, iron atoms and phosphorus atoms is (1.01-1.10):(0.960-0.975):1.
[0042] As a preferred embodiment, in step (1), the residual carbon content of the carbon source is 1.0wt.% to 1.5wt.% of the theoretical output of lithium iron phosphate; in some more preferred embodiments, the added amount of the carbon source is 10% to 15% of the sum of the masses of the phosphorus source, the iron source and the lithium source.
[0043] As a preferred embodiment, in step (1), the additive is added in an amount of 2000ppm to 4000ppm of the sum of the masses of the phosphorus source, the iron source and the lithium source.
[0044] As a preferred embodiment, in step (1), the grinding includes but is not limited to ball milling, vibration milling, ultrasonic grinding and the like; it is understandable that mixing the reaction raw materials by grinding can not only play the role of mixing the reaction raw materials evenly, but also play the role of refining the particle size of the raw materials, thereby facilitating the uniformity of the lithium manganese iron phosphate particles obtained by subsequent sintering.
[0045] As a preferred embodiment, in step (1), the D50 particle size of the mixed slurry obtained by the grinding is 0.40 μm to 0.42 μm, including but not limited to any one of 0.40, 0.402, 0.405, 0.408, 0.41, 0.412, 0.415, 0.418, 0.42 (μm) or a numerical range consisting of any two of them.
[0046] As a preferred embodiment, in step (1), the present invention does not impose any restriction on the diversion ratio of the first slurry and the second slurry; it is understandable that the present invention is based on two different treatments of the mixed slurry. In some optional industrial processes, those skilled in the art can use a batch of the mixed slurry for the operation of the first slurry in step (2), and use another batch of the mixed slurry for the operation of the second slurry in step (3); therefore, in the present invention, the corresponding technical effect can be achieved simply by limiting the amount of the first spray material and the second spray material that appear later.
[0047] As a preferred embodiment, in step (2), the first spray treatment is a low-frequency spray treatment; the inlet air temperature of the first spray treatment is 210°C to 250°C, the outlet air temperature of the first spray treatment is 85°C to 105°C, and the frequency of the first spray treatment is 30Hz to 35Hz.
[0048] As a preferred embodiment, in step (3), the second spray treatment is a high-frequency spray treatment; the inlet air temperature of the second spray treatment is 210°C to 250°C, the outlet air temperature of the second spray treatment is 85°C to 105°C, and the frequency of the second spray treatment is 45Hz to 50Hz.
[0049] As an optional embodiment, the air inlet temperature of the first spray treatment and / or the second spray treatment includes but is not limited to any one of 210, 215, 220, 225, 230, 235, 240, 245, 250 (℃) or a numerical range formed by any two of them, and the air outlet temperature of the first spray treatment and / or the second spray treatment includes but is not limited to any one of 85, 90, 95, 100, 105 (℃) or a numerical range formed by any two of them.
[0050] As an optional embodiment, the frequency of spray drying refers to the number of times the spray drying equipment completes the spray operation per unit time, or can be understood as the periodicity of the spray operation; in the present invention, two spraying methods with significantly different frequencies can be used to obtain two spray materials with significantly different particle sizes; the frequency of the first spray treatment includes but is not limited to any one of 30, 31, 32, 33, 34, 35 (Hz) or a numerical range composed of any two of them, and the frequency of the second spray treatment includes but is not limited to any one of 45, 46, 47, 48, 49, 50 (Hz) or a numerical range composed of any two of them.
[0051] As a preferred embodiment, the surfactant includes at least one of vinyl bisstearamide, glyceryl monostearate or polyurethane; wherein the molecular weight of the vinyl bisstearamide is 593.0222, the molecular weight of glyceryl monostearate is 358.56, and the molecular weight of the polyurethane is 302.37.
[0052] As a preferred embodiment, the added amount of the surfactant is 0.5wt.% to 1wt.% of the second slurry; in some optional embodiments, after adding the surfactant, sufficient mixing is carried out, and stirring is used to assist in uniform mixing, and the stirring time can be referenced to 0.8h to 1.5h.
[0053] As a preferred embodiment, it is clear in the art that spray drying is a process for preparing powder particles by spraying a solution or suspension into mist and rapidly drying it in a hot air flow. Due to the influence of surface tension, vortex force and drying during the spraying process, the particles obtained after spray drying are usually spherical. Therefore, it has been tested that the spherical particle size of the first spray material is 45μm to 50μm in diameter, and the spherical particle size of the second spray material is 25μm to 30μm.
[0054] As a preferred embodiment, in step (4), the mass ratio of the first spray material to the second spray material is (3-4): (1-2); that is, based on the total mass of 100%, the first spray material is 60wt.%-80wt.%, and the second spray material is 20wt.%-40wt.%.
[0055] As a preferred embodiment, in step (4), the sintering temperature is 750°C to 780°C, and the sintering time is 8h to 12h; in some optional embodiments, the sintering temperature includes but is not limited to any one of 750, 755, 760, 765, 770, 775, 780 (°C) or a numerical range formed by any two of them, and the sintering time includes but is not limited to any one of 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, 12 (h) or a numerical range formed by any two of them.
[0056] As a preferred embodiment, in step (4), the sintering is carried out under an inert atmosphere; the inert atmosphere includes but is not limited to nitrogen, helium, neon or argon.
[0057] As a preferred embodiment, in step (4), after the pulverization, the median particle size of the lithium manganese iron phosphate is 0.8 μm to 1.6 μm.
[0058] The second aspect of the present invention is to provide lithium iron phosphate prepared by the method for preparing the lithium iron phosphate positive electrode material as described in the first aspect.
[0059] A third aspect of the present invention is to provide a lithium ion battery.
[0060] The lithium-ion battery includes the lithium iron phosphate as described in the second aspect. It is understandable that the lithium iron phosphate is the active ingredient of the positive electrode of the lithium-ion battery, or one of the active ingredients of the positive electrode of the lithium-ion battery; the positive electrode of the lithium-ion battery may also include structural elements or functional components such as conductive agents, binders, and current collectors; the lithium-ion battery also includes a negative electrode, an electrolyte, a diaphragm, and other necessary or non-essential functional elements or packaging components, etc., which can be arbitrarily selected and combined by those skilled in the art; when the lithium iron phosphate described in the present invention is included in the lithium-ion battery, it can be regarded as an embodiment of the present invention. The specific selection of the negative electrode, diaphragm and electrolyte in the lithium-ion battery is not limited in the present invention.
[0061] A fourth aspect of the present invention is to provide an electrical device.
[0062] The electrical equipment includes the lithium-ion battery. The electrical equipment can be any equipment or device that relies on electric energy to work or operate, including but not limited to new energy vehicles, building electrical equipment, industrial electrical appliances, household and agricultural electrical appliances, etc. When the lithium-ion battery is included, any electrical equipment equipped with the lithium-ion battery can belong to an embodiment of the present invention.
[0063] Example 1
[0064] (1) Weigh 4000 g of iron phosphate, 1000 g of lithium carbonate, 140 g of sucrose, 350 g of polyethylene glycol, and 10 g of titanium dioxide, add 6 L of deionized water and mix, and grind the mixed slurry in a first sand mill for 1 h and then transfer it to a second sand mill for fine grinding until the slurry D50 is 0.41 μm.
[0065] (2) The slurry was divided into two parts, the mass ratio of the first slurry to the second slurry was 2.5:1, 10 g of glyceryl monostearate was added to the second slurry and stirred at high speed for 1 hour.
[0066] (3) The two slurries were spray dried separately, with an inlet air temperature of 220°C and an outlet air temperature of 90°C. The second slurry was sprayed at 50 Hz to collect 450 g of spray material, and the secondary particle size D50 was 27 μm. The first slurry was sprayed at 35 Hz to collect 1150 g of spray material, and the secondary particle size D50 was 46 μm. The spray materials with different secondary particle sizes were mixed in a V-type mixer for 6 hours.
[0067] (4) The mixed spray material was placed in a nitrogen atmosphere for high temperature sintering at a temperature of 770°C for 9 hours. After cooling in the furnace, it was crushed to obtain a lithium iron phosphate material with a D50 of 1.12 μm.
[0068] Example 2
[0069] The method is basically the same as Example 1, except that the titanium dioxide in step (1) is replaced by zirconium oxide of the same molar amount.
[0070] Example 3
[0071] The method is basically the same as Example 1, except that the glyceryl monostearate in step (2) is replaced by the same molar amount of vinyl bisstearamide.
[0072] Example 4
[0073] It is basically the same as Example 1, except that:
[0074] Step (3): The first slurry is spray-dried at 30 Hz, and the corresponding secondary particle size D50 is 25 μm; the second slurry is spray-dried at 45 Hz, and the corresponding secondary particle size D50 is 45 μm.
[0075] Example 5
[0076] The method is basically the same as Example 1, except that the sintering conditions in step (4) are replaced by 750° C. and 12 h. After cooling in the furnace, the material is crushed to obtain a lithium iron phosphate material with a D50 of 0.98 μm.
[0077] Example 6
[0078] The method is basically the same as Example 1, except that the sintering conditions in step (4) are replaced with 780° C. and 8 h. After cooling in the furnace, the material is crushed to obtain a lithium iron phosphate material with a D50 of 1.34 μm.
[0079] Comparative Example 1
[0080] The method is basically the same as Example 1, except that the addition of glyceryl monostearate in step (2) is omitted.
[0081] Comparative Example 2
[0082] The method is basically the same as Example 1, except that step (2) is cancelled and step (3) is replaced by spray drying the slurry, with an inlet air temperature of 220°C, an outlet air temperature of 90°C, and 440 g of spray material collected at 50 Hz. The secondary particle size D50 is 28 μm.
[0083] The lithium iron phosphate material obtained in Example 1 was subjected to particle size distribution detection and scanning electron microscope test, and the following results were obtained: Figure 1 The particle size distribution diagram shown in Figure 2 The SEM image shown. Further, Table 1 provides the particle size and compaction density of the lithium iron phosphate materials obtained in each embodiment and comparative example.
[0084] Table 1
[0085]
[0086]
[0087] Test example
[0088] First, the lithium iron phosphate material obtained in the above embodiments and comparative examples and the conductive agent Super P and binder PVDF were dispersed in NMP at a mass ratio of 96:2:2. After being evenly dispersed, they were coated on aluminum foil and vacuum dried to obtain a positive electrode. Further, a polypropylene film was used as a separator, lithium hexafluorophosphate was used as an electrolyte, and a lithium metal sheet was used as a negative electrode. The sheet-shaped positive electrode material, lithium metal sheet, separator, and electrolyte were assembled into a button cell for testing. The discharge specific capacity of each button cell at 0.1C was tested by an electrochemical workstation, and the results are shown in Table 2.
[0089] Table 2
[0090]
[0091]
[0092] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A method for preparing a lithium iron phosphate positive electrode material, characterized in that: The steps include: (1) preparing a solution containing a phosphorus source, an iron source, a lithium source, a carbon source and an additive, and grinding the solution to obtain a mixed slurry; dividing the mixed slurry into a first slurry and a second slurry; (2) subjecting the first slurry to a first spraying treatment to obtain a first spray material; (3) after the second slurry is fully mixed with a surfactant, a second spraying treatment is performed to obtain a second spray material; (4) The first spray material and the second spray material are mixed, sintered, and crushed to obtain lithium iron phosphate.
2. The method for preparing the lithium iron phosphate positive electrode material according to claim 1, characterized in that: Satisfy at least one of the following characteristics (a) to (e): (a) the phosphorus source comprises at least one of iron phosphate, lithium monohydrogen phosphate, lithium dihydrogen phosphate, ammonium phosphate or ammonium dihydrogen phosphate; (b) the iron source comprises at least one of ferric phosphate, ferric oxide, ferroferric oxide, ferric citrate or ferrous oxalate; (c) the lithium source comprises at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium citrate or lithium dihydrogen phosphate; (d) the carbon source comprises at least one of glucose, sucrose, citric acid, polyethylene glycol, starch or cellulose; (e) The additive includes at least one element selected from the group consisting of titanium, niobium, magnesium and zirconium.
3. The method for preparing the lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the solution of step (1), the molar ratio of lithium atoms, iron atoms and phosphorus atoms is (1.01-1.10):(0.960-0.975):
1.
4. The method for preparing a lithium iron phosphate positive electrode material according to claim 1, characterized in that: The D50 particle size of the mixed slurry is 0.40 μm to 0.42 μm; and / or, the average diameter of the first spray material is 45 μm to 50 μm; And / or, the average diameter of the second spray material is 25 μm to 30 μm.
5. The method for preparing the lithium iron phosphate positive electrode material according to claim 1, characterized in that: The mass ratio of the first spray material to the second spray material is (3-4):(1-2).
6. The method for preparing a lithium iron phosphate positive electrode material according to claim 1, characterized in that: The inlet air temperature of the first spray treatment and / or the second spray treatment is 210°C to 250°C, and the outlet air temperature is 85°C to 105°C; The frequency of the first spray treatment is 30 Hz to 35 Hz; The frequency of the second spray treatment is 45 Hz to 50 Hz.
7. The method for preparing a lithium iron phosphate positive electrode material according to claim 1, characterized in that: The sintering temperature is 750° C. to 780° C., and the sintering time is 8 h to 12 h.
8. Lithium iron phosphate obtained by the method for preparing a lithium iron phosphate positive electrode material according to any one of claims 1 to 7.
9. A lithium ion battery, characterized in that: Comprising the lithium iron phosphate as described in claim 8.
10. An electrical device, characterized in that: Comprising the lithium ion battery as claimed in claim 9.